You are Here: Home

1. (Original post by elpaw)
there is a "proof" but not a proof.
Now that is worrying for Maths sake...
2. (Original post by bono)
Now that is worrying for Maths sake...
the "proof" isn't a proof because it's faulty.
3. (Original post by elpaw)
there is a "proof" but not a proof.
Its more of a trick isn't it? Taking 0 to be a non variable or is it a constant? So the trick suceeds
4. (Original post by elpaw)
the "proof" isn't a proof because it's faulty.
Is it mathematically incorrect then?
5. (Original post by 2776)
Its more of a trick isn't it? Taking 0 to be a non variable or is it a constant? So the trick suceeds
Could you show me this?
6. let a = b
=> a² = ab
=> a² + a²-2ab = ab + a²-2ab
=> 2(a²-ab) = (a²-ab)
=> 2 = 1
7. Just for the dim-witted amongst us, the problem with elpaw's "proof" is that a^2-ab=0 as a=b. You can't divide by zero and get a defined answer.
8. (Original post by chrisbphd)
Just for the dim-witted amongst us, the problem with elpaw's "proof" is that a^2-ab=0 as a=b. You can't divide by zero and get a defined answer.
i know. i already said it was incorrect.
9. You might find this interesting.

Classic Fallacies
10. (Original post by elpaw)
let a = b
=> a² = ab
=> a² + a²-2ab = ab + a²-2ab
=> 2(a²-ab) = (a²-ab)
=> 2 = 1

Ahhh yes, I see now Chris!!
11. Of course, both sides equal zero, which means that the proof doesnt hold. But its quite clever anyway.
12. (Original post by elpaw)
i know. i already said it was incorrect.
I wasn't disputing that...I was just explaining to others.
13. (Original post by chrisbphd)
I wasn't disputing that...I was just explaining to others.
Me too.
14. That ladder thing is pretty sweet. But it is more of a physical thing than theoretical.
15. (Original post by elpaw)
let a = b
=> a² = ab
=> a² + a²-2ab = ab + a²-2ab
=> 2(a²-ab) = (a²-ab)
=> 2 = 1
Bono doesn't seem to get it:

First line is multiplying both sides by a
Then add (a²-2ab) to both sides
Then simplify
Then divide both sides by a²-2ab
BUT dividing by a²-2ab is dividing by 0 if a=b, so you get an undefined on both sides, not 2 and 1.
16. (Original post by ZJuwelH)
Bono doesn't seem to get it:

First line is multiplying both sides by a
Then add (a²-2ab) to both sides
Then simplify
Then divide both sides by a²-2ab
BUT dividing by a²-2ab is dividing by 0 if a=b, so you get an undefined on both sides, not 2 and 1.
Cheers.
17. (Original post by chrisbphd)
You might find this interesting.

Classic Fallacies
the "all people in canada are the same age" one is really compelling.
18. 4.45 isn't it obvious?
19. (Original post by elpaw)
the "all people in canada are the same age" one is really compelling.
Yeah I liked that, I got it straight away, what if G is just P and Q, I'm a logical genius!... OK maybe not...
20. (Original post by ogs)
4.45 isn't it obvious?
apparently it isnt, because it's 4.44

TSR Support Team

We have a brilliant team of more than 60 Support Team members looking after discussions on The Student Room, helping to make it a fun, safe and useful place to hang out.

This forum is supported by:
Updated: March 2, 2004
Today on TSR

Get the low down

### University open days

• University of Exeter
Wed, 24 Oct '18
Wed, 24 Oct '18
• Northumbria University